Innovations in the Netherlands: a time dynamic analysis - van der WEIJ, George (European Spatial Research and Policy, 1994)
This article covers several aspects of innovations within firms in the Netherlands. First of all the innovativeness of the Dutch industry is investigated. This is done by means of a measuring scheme developed by the Faculty of Spatial Sciences of the University of Groningen. The next step will be to analyze the spatial distribution of innovative firms in the Netherlands. A special feature of this investigation is the possibility to compare the present situation with the one in 1983 when a comparable research was conducted. In this way the spatial temporal paltem can be analyzed. Furthermore some attention is paid to employment implications of innovations.